OBTAINING A RECOMBINANT FORM OF PLANT DEFENSIN FROM NIGELLA SATIVA - Tsoy V.E; Dalimova D.A; Ibragimova Sh.N; Muminov M.I; Yakubov M.D; Turdikulova Sh.U (Western European Studies, 2024)
Today, one of the challenges facing modern agriculture is crop loss due to various biotic and abiotic factors. We investigated defensins, which are an important component of the plant's defense system and form protective antimicrobial barriers between different types of tissues and organs of plants, as well as around seeds. The aim of our research was to obtain a recombinant form of plant defensin with antimicrobial activity. A recombinant DNA vector construct pRSET_A was obtained with the cloned Ns-D2 defensin gene under a regulatable promoter, a histidine tag, and an enterokinase site. The resulting construct can be used for defensin synthesis, which can be employed to combat pests of agricultural crops.
Keywords: Defensins; Peptides; Fungicidal And Antimicrobial Activity